Numerical simulation of AA7075 under high strain rate with different shape of striker of split Hopkinson Pressure bar. (March 2021) - Gupta, Manish Kumar
Graphical abstract: Abstract: The high strain rate characterization of materials have always remained an essential to know the exact behaviour in dynamic conditions, such as blasts, earthquakes, projectile penetrations, crashworthiness of vehicles, bullet proof armours. These high strain rate characterizations can be done using experimental technique such as Split Hopkinson Pressure Bar (SHPB) Test. These experimental techniques are very costly and difficult to conduct. However, the behaviour of materials under dynamic loading can be performed under high strain rate using finite element simulation of SHPB Test. The numerical simulations of AA7075 under different shape and velocity of striker in dynamic conditions are performed utilizing ABAQUS/Explicit 6.14. To understand the effect of shape, striker bar's shape is varying from circular to square while its length is kept constant as 200 mm. Furthermore, impact velocity is also varied from 20 to 50 m/s to see the effect of velocity under large strain rates. The test specimen's shapes are also of varying cross-section to understand the effect of shape of specimen under dynamic conditions. Results stated that the wave's amplitude and duration are dependent to the striker parameters. Specimen shape also affects the flow behaviour of specimen.